Upogibanje verižnih členov - Legat, Franc (Kovine zlitine tehnologije, 1997)
Different method of chain links bending are described in dependence upon the steel tensile strength and rod diameter, as: cold and hot bending. Also the modification of steel properties and the critical points, where cracks appear by bending are discussed.
Keywords: stroji; verige; oblikovanje; toplotna obdelava; jekla